INTRACRANIAL HAEMANGIOPERICYTOMA: A VERY RARE ENTITY HAVING A HIGH MALIGNANT/METASTATIC POTENTIAL - Ahmad, Manzoor; Majid, Abdul; Masood, Misbah (Journal of Ayub Medical College Abbottabad, 2009)
Intracranial haemangiopericytomas are very rare tumours. Their radiological appearance resembles that of meningioma. Recommended treatment is total surgical excision, if possible, followed by radiotherapy. A vigilant, long term clinical and radiological follow up is very essential due to a high rate of late onset recurrence along with neural and extraneural metastases. A case report and review of literature is presented. Keywords: Intracranial haemangiopericytoma, recurrence, radiotherapy, metastasis